2005
DOI: 10.1073/pnas.0409845102
|View full text |Cite
|
Sign up to set email alerts
|

A shortened adeno-associated virus expression cassette for CFTR gene transfer to cystic fibrosis airway epithelia

Abstract: Adeno-associated viruses (AAVs) such as AAV5 that transduce airway epithelia from the apical surface are attractive vectors for gene transfer in cystic fibrosis (CF). However, their utility in CF has been limited because packaging of the insert becomes inefficient when its length exceeds Ϸ4,900 -5,000 bp. To partially circumvent this size constraint, we previously developed a CF transmembrane conductance regulator (CFTR) transgene that deleted a portion of the R domain (CFTR⌬R). In this study, we focused on sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 47 publications
2
78
0
Order By: Relevance
“…4F). This is in contrast to AAV2, which does not correct this model, and AAV5, which requires a substantially higher multiplicity of infection (MOI) (26). Furthermore, a dose-response with AAV2.5T-CFTR⌬R in CF epithelia showed, surprisingly, that as little as 10 vg/cell was sufficient for chloride transport correction, and a dose of 100-1000 vg/cell was equivalent to adenovirus carrying the wild-type CFTR gene (Fig.…”
Section: Library Construction and Selection Results In A Novel Aav Withmentioning
confidence: 93%
See 3 more Smart Citations
“…4F). This is in contrast to AAV2, which does not correct this model, and AAV5, which requires a substantially higher multiplicity of infection (MOI) (26). Furthermore, a dose-response with AAV2.5T-CFTR⌬R in CF epithelia showed, surprisingly, that as little as 10 vg/cell was sufficient for chloride transport correction, and a dose of 100-1000 vg/cell was equivalent to adenovirus carrying the wild-type CFTR gene (Fig.…”
Section: Library Construction and Selection Results In A Novel Aav Withmentioning
confidence: 93%
“…We next investigated potential therapeutic applications of AAV2.5T by analyzing whether it could efficiently express CFTR and correct the CF chloride transport defect. CF airway epithelia were transduced with AAV2.5T encoding a shortened CFTR expression cassette (CFTR⌬R, 50,000 vg/cell), then analyzed in Ussing chambers 30 days posttransduction, as previously described (26,27). Normal epithelia demonstrated chloride transport (Fig.…”
Section: Library Construction and Selection Results In A Novel Aav Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistent expression could be useful for long-term therapy of chronic lung diseases such as CF; and recent studies have shown that rAAV5/5 vectors can be used to correct CF chloride transport defects in airway epithelial cells grown in culture. 51 However, data presented here suggest that when rAAV5/5 is delivered to the mouse lung, it is unlikely to efficiently transduce airway cells which are the target for gene therapy of CF lung disease. In addition, animals demonstrating persistent luciferase expression for many months demonstrated a high level of anti-rAAV5 antibodies, including neutralizing antibodies, in serum (Figure 3), suggesting that it might be difficult to repeatedly administer rAAV5/5 for treatment of chronic conditions.…”
Section: Discussionmentioning
confidence: 91%